Silencing of RpATG8 impairs the biogenesis of maternal autophagosomes in vitellogenic oocytes, but does not interrupt follicular atresia in the insect vector Rhodnius prolixus. - Jéssica Pereira; Calebe Diogo; Ariene Fonseca; Larissa Bomfim; Pedro Cardoso; Anna Santos; Uilla Dittz; Kildare Miranda; Wanderley de Souza; Adriana Gioda; Enrique R D Calderon; Luciana Araripe; et al. (PLoS Neglected Tropical Diseases)
Follicular atresia is the mechanism by which the oocyte contents are degraded during oogenesis in response to stress conditions, allowing the energetic resources stored in the developing oocytes to be reallocated to optimize female fitness. Autophagy is a conserved intracellular degradation pathway where double-membrane vesicles are formed around target organelles leading to their degradation after lysosome fusion. The autophagy-related protein 8 (ATG8) is conjugated to the autophagic membrane and has a key role in the elongation and closure of the autophagosome. Here we identified one single isoform of ATG8 in the genome of the insect vector of Chagas Disease Rhodnius prolixus (RpATG8) and found that it is highly expressed in the ovary during vitellogenesis. Accordingly, autophagosomes were detected in the vitellogenic oocytes, as seen by immunoblotting and electron microscopy. To test if autophagosomes were important for follicular atresia, we silenced RpATG8 and elicited atresia in vitellogenic females by Zymosan-A injections. We found that silenced females were still able to trigger the same levels of follicle atresia, and that their atretic oocytes presented a characteristic morphology, with accumulated brown aggregates. Regardless of the difference in morphology, RpATG8-silenced atretic oocytes presented the same levels of protein, TAG and PolyP, as detected in control atretic oocytes, as well as the same levels of acidification of the yolk organelles. Because follicular atresia has the ultimate goal of restoring female fitness, we tested if RpATG8-silenced atresia would result in female physiology and behavior changes. Under insectarium conditions, we found that atresia-induced control and RpATG8-silenced females present no changes in blood meal digestion, survival, oviposition, TAG content in the fat body, haemolymph amino acid levels and overall locomotor activity. Altogether, we found that autophagosomes are formed during oogenesis and that the silencing of RpATG8 impairs autophagosome biogenesis in the oocytes. Nevertheless, regarding major macromolecule degradation and adaptations to the fitness costs imposed by triggering an immune response, we found that autophagic organelles are not essential for follicle atresia in R. prolixus.